ANALISIS PERSEPSI KARYAWAN RRI PADANG TERHADAP PENGGUNAAN APLIKASI SIM-INTEGRATED SOFTWARE SYSTEM (Studi Kasus Menggunakan TAM diperluas) - Yully Eka Fitri; Zulhendra Zulhendra; Asrul Huda (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2018)
This study aims to determine (1) perceived easy of use, perceived usefulness, attitude towards using, behavioral intention to use, real use of a system ( actual system use) as well as variables to be developed that is perceived compatibility (perceived compatibility) to the level of user acceptance Management Information System Integrated Software System (ISS). (2) To know the influence of five variables contained in Technology Acceptance Model and one variable that will be developed model together to the level of user acceptance Management Information System in RRI Padang. This type of research is descriptive and correlational. The population of this research is employees of RRI Padang. Sampling technique using proportional stratified random sampling with the number of samples of 50 people. Data analysis techniques are: descriptive analysis and inductive analysis, ie normality test, homogeneity test, and linearity test. The result of data analysis shows: perceived easy of use variable, perceived usefulness, attitude toward using, behavioral intention to use, actual system use, perceived compatibility together significantly influence 66,4% toward acceptance level of Integrated Software System Management Information System ISS) at RRI Padang. So it can be concluded that perceived easy of use factors, perceived usefulness, attitude toward using, behavioral intention to use, actual system use, and perceived compatibility have contributed to the acceptance level of the system. If each variable has a higher correlation it will increase the acceptance of Management Information Systems Integrated Software System (ISS) in RRI Padang. Keywords : Technology Acceptance Model (TAM), perceived ease of use, perceived usefulness, attitude toward using, behavioral intention to use, perceived compatibility, actual system use,  Management Information System Integrated Software System (ISS)